2019
DOI: 10.1111/liv.14054
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide estimates and risk factors of hospital readmission in patients with cirrhosis in the United States

Abstract: Background The burden of cirrhosis on the healthcare system is substantial and growing. Our objectives were to estimate the readmission rates and hospitalization costs as well as to identify risk factors for 90‐day readmission in patients with cirrhosis. Methods We conducted a weighted analysis of the 2014 Nationwide Readmission Database to identify adult patients with cirrhosis‐related complications in the United States and assessed readmission rates at 30, 60 and 90 days post‐index hospitalization. Predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…However, our research involved a population‐based study that captured all readmissions within the health care system. A previous study in the United States, which conducted a weighted analysis of the 2014 Nationwide Readmissions Database, reported a readmission rate of 15%, and the main causes of readmission were complications of cirrhosis . Likewise, our data support that cirrhosis is a major economic burden in the health care system, because after initial admission most patients are readmitted again in the health care system.…”
Section: Discussionsupporting
confidence: 78%
“…However, our research involved a population‐based study that captured all readmissions within the health care system. A previous study in the United States, which conducted a weighted analysis of the 2014 Nationwide Readmissions Database, reported a readmission rate of 15%, and the main causes of readmission were complications of cirrhosis . Likewise, our data support that cirrhosis is a major economic burden in the health care system, because after initial admission most patients are readmitted again in the health care system.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, inability to identify re‐admissions is one of the limitations of NIS dataset. A recent study utilizing the Nationwide Readmission Database reported that 25% of patients with cirrhosis are re‐admitted with liver‐related complication within 90 days . Therefore, our results are limited by the fact that we were unable to exclude patients who were re‐admitted.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study utilizing the Nationwide Readmission Database reported that 25% of patients with cirrhosis are re-admitted with liver-related complication within 90 days. 29 Therefore, our results are limited by the fact that we were unable to exclude patients who were re-admitted. Since the cause of in-hospital mortality was not available in the NIS database, we are unable to Abbreviations: CI, confidence interval; NAFLD, non-alcoholic fatty liver disease; OR, odds ratio.…”
Section: Discussionmentioning
confidence: 96%
“…90‐day transition percentages for staying alive without admission/LT was 50%, 4% for LT, 3% for death and 40% for admissions (range 25%‐60%). The estimate for hospitalisations was made from an admixture of several studies in outpatients and inpatients …”
Section: Methodsmentioning
confidence: 99%
“…Patients with cirrhosis have a complicated natural history characterised by admissions and readmissions over time . These admissions and readmissions in cirrhosis are prevalent and are a major cause of healthcare expenditure . However, prediction models using clinical biomarkers alone are largely suboptimal, with relatively low c‐statistics in population‐based and cohort studies .…”
Section: Introductionmentioning
confidence: 99%